Correlation of Characteristics and Knowledge Level with the Prevalence of Anemia Among Female Adolescents - Yulvia, Novrita Tri; Qonita, Qonita (Ahmar Metastasis Health Journal, 2025)
Anemia is a prevalent health issue among adolescent girls, particularly during puberty, when iron requirements increase due to growth and menstruation. This study aimed to analyze the relationship between adolescent characteristics, knowledge levels, and the incidence of anemia among female students at SMP NU Jawilan, Serang Regency. Using a quantitative analytic design with a cross-sectional approach, data were collected from 57 students through questionnaires and hemoglobin measurements using a Hemocue device. The variables examined included knowledge level, menstrual cycle, menstruation duration, nutritional status, dietary patterns, and sleep patterns. Chi-Square tests revealed significant relationships between all variables and the incidence of anemia, with p-values less than 0.05. The findings indicate that inadequate knowledge, irregular or prolonged menstruation, poor nutritional status, unhealthy diets, and poor sleep habits are strongly associated with anemia among adolescent girls. These results highlight the need for targeted health education, nutritional interventions, and lifestyle improvements to reduce anemia prevalence in this population. School-based programs involving health workers, teachers, and parents are essential to foster better health behaviors and prevent anemia during adolescence.